Thomas Reid on society and politics - Reid, Thomas, 1710-1796 (Reid, Thomas, 1710-1796. Works. 1996 ;, 2014)
Thomas Reid published almost nothing on politics, but his manuscripts show that he was deeply concerned with social, political and economic issues throughout his career. Collected together here for the first time, Reid's Glasgow lecture notes and his papers to learned societies in Aberdeen and Glasgow show that he was an acute commentator on contemporary politics and that he used his philosophy to formulate solutions to some of the practical political and economic problems of his day. Opens up a different Enlightenment from that of David Hume and Adam Smith, Reid's predecessor in the Glasgow chair of moral philosophy Explores Reid's eclectic system of political economy, which had considerable affinities with the work of Sir James Steuart Illustrates an original use of traditional and contemporary ideas in European political thought, especially those of More, Harrington and Montesquieu Traces the political implications of Reid's common sense philosophy Includes a contextualising and critical introduction All of the manuscripts are fully annotated with explanatory and textual notes